Indonesian Journalist; After Political Reformation - Triputra, Pinckey (European Scientific Journal, ESJ, 2017)
For the first time ever, 385 professional journalists in Indonesia have been surveyed, by means of face-to-face interviews, for their basic characteristics and their views on professional values. The findings suggest that the ‘typical’ Indonesian journalist is young, male, well educated and earns an above-average salary. In terms of education and training, journalists of the archipelago are becoming increasingly professional. They see themselves as neutral and objective disseminators of news, though not as political actors and agents of development. Indonesian journalists disapprove of unscrupulous practices of reporting, yet many of them justify and practice corruption during their everyday work. Although the study’s primary focus is on Indonesia, the analysis goes well beyond national boundaries. By subjecting the data to factor analysis, five dimensions of media roles could be extracted, namely public-oriented news journalism, popular service journalism, critical watchdog journalism, objective precision journalism and opinion-oriented news journalism.